Selenium-mediated modulation of cadmium and lead stress in black gram and rice seedlings - Behera, Kambaska Kumar; Sanghamitra, Priyadarshani (ORYZA-An International Journal of Rice, 2026)
Cadmium (Cd) and lead (Pb) are pervasive environmental contaminants that severely affect plant health, productivity, and food safety. This study evaluated the effects of Cd and Pb stress on biomass production, pigment composition, biochemical parameters, antioxidant enzyme activity, and metal accumulation in black gram (Vigna mungo (L.) Hepper, cv. Prasad) and rice (Oryza sativa cv. Khandagiri) seedlings grown under hydroponic conditions, with a focus on the ameliorative effects of selenium (Se). Both metals caused significant reductions in biomass, chlorophyll content, protein levels, and soluble sugars, while enhancing proline accumulation and antioxidant enzyme activities (POX, CAT, and SOD), particularly in root tissues. Selenium supplementation effectively alleviated metal-induced stress by restoring pigment and protein levels, improving sugar content, enhancing antioxidative responses, and reducing Cd and Pb accumulation in shoot tissues. Metal tolerance indices, bioconcentration factor (BCF), total accumulation rate (TAR), tolerance index (Ti), and transportation index (TI)-were significantly improved under Se co-treatment. Comparative analysis revealed that rice exhibited slightly greater physiological resilience and metal handling capacity than black gram. These results highlight selenium's protective potential in alleviating Cd and Pb toxicity through the modulation of antioxidant defense mechanisms and metal homeostasis, offering promising applications for improving crop tolerance and ecological safety in metal-contaminated environment.